Availability of On-Site Child Care and its Impact on Productivity and Organizational Commitment: A Study on Female Knowledge Workers in Bangladesh - Chowdhury, Kishwar Mubin (AIUB Journal of Business and Economics, 2018)
With the increasing percentage of female knowledge workers entering the workforce in recent times in Bangladesh, it is becoming increasingly important to facilitate the highest possible output from this emerging segment. Availability of childcare support for working mothers is one of the most prominent issues concerning working women in Bangladesh. While developmental and non-government organizations have made major leaps in ensuring on-site child care facilities for thousands of women in the garments sector, other sectors are far behind. The purview of this research, therefore, will be contained within a sample of female knowledge workers who are mothers and the challenges they face regarding child care support which possibly hinder their productivity at work and prevent them from making similar contributions as their male counterparts in similar positions. The research concludes on significant findings on the impact of on-site childcare on female knowledge worker productivity and organizational commitment and offers recommendations to encourage the provision of on-site childcare for companies wishing to capitalize on the time contributed by female knowledge workers at the office.